2(x+5)+3(x-2)=64

Simple and best practice solution for 2(x+5)+3(x-2)=64 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+5)+3(x-2)=64 equation:


Simplifying
2(x + 5) + 3(x + -2) = 64

Reorder the terms:
2(5 + x) + 3(x + -2) = 64
(5 * 2 + x * 2) + 3(x + -2) = 64
(10 + 2x) + 3(x + -2) = 64

Reorder the terms:
10 + 2x + 3(-2 + x) = 64
10 + 2x + (-2 * 3 + x * 3) = 64
10 + 2x + (-6 + 3x) = 64

Reorder the terms:
10 + -6 + 2x + 3x = 64

Combine like terms: 10 + -6 = 4
4 + 2x + 3x = 64

Combine like terms: 2x + 3x = 5x
4 + 5x = 64

Solving
4 + 5x = 64

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 5x = 64 + -4

Combine like terms: 4 + -4 = 0
0 + 5x = 64 + -4
5x = 64 + -4

Combine like terms: 64 + -4 = 60
5x = 60

Divide each side by '5'.
x = 12

Simplifying
x = 12

See similar equations:

| 4x^3+15x^2+3x+28=0 | | 4x^2+15x+3=0 | | 2x*5y=50 | | -5/16/25/8= | | 5/8-(1/2-3/4)= | | 10(-3+-2t)+10+-2(6t+-13)=0 | | x(x^2-9)=0 | | 10(-3-2t)+10-2(6t-13)=3 | | -0.2x^2+0.1x=-0.06 | | -5z^2-4z+3=0 | | 4(64)+12=0 | | -18x+4y=74 | | X+x-3+x+5=35 | | x(x^2-25)=0 | | 5(x-6)+6=7x-6 | | X+(x+5)+(x-3)=35 | | x(x+5)(x-1)=0 | | 6-6x=5x-8x+15 | | x^2+y^2+z=1 | | 5(6y-4)+19=3(4y+4)+7 | | 3(2y-4)+18=4(3y+1)+1 | | x^2+y^2-z=1 | | 7x-3=2x-5 | | 14x-20-13x=-14 | | 6x+7x-76=95-6x | | 105=(p^2-p) | | -18x-13=15x-4 | | x^2-37x-120=0 | | s=(p^2-p) | | 8x+4=4x+6 | | 9(x+4)+2=-9(x-8)-6 | | 7x+3=6(x+8)-8 |

Equations solver categories